Visual outcome measures in clinical trials of remyelinating drugs - Riboni-Verri, Gioia; Chen, Benson S; McMurran, Christopher E; Halliwell, Gregory J; Brown, J William L; Coles, Alasdair J; Cunniffe, Nick G (BMJ neurology open, 2024)
One of the most promising approaches to delay, prevent or reverse disability progression in multiple sclerosis (MS) is to enhance endogenous remyelination and limit axonal degeneration. In clinical trials of remyelinating drugs, there is a need for reliable, sensitive and clinically relevant outcome measures. The visual pathway, which is frequently affected by MS, provides a unique model system to evaluate remyelination of acute and chronic MS lesions in vivo and non-invasively. In this review, we discuss the different measures that have been used and scrutinise visual outcome measure selection in current and future remyelination trials.